2019
DOI: 10.1016/j.jses.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative indications for total shoulder arthroplasty predict adverse postoperative complications

Abstract: Background Although studies have shown improved pain, function, and patient satisfaction after total shoulder arthroplasty (TSA), preoperative factors predicting poor outcomes are unexplored. Comparison of postoperative complications between osteoarthritis (OA), cuff arthropathy (CA), and fracture patients is important for identifying at-risk patients. Methods Primary TSAs from 2014 to 2016 with preoperative OA, CA, and proximal humerus fractures as indications were que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…In complex proximal humerus fractures, which represent the third-most common fracture seen in patients aged > 60 years [30], rTSA was found to provide more reproducible function with better recovery, as well as lower revision rates than HA [31,32]. However, recent studies also suggest, that shoulder arthroplasty due to fracture could be associated with more inconsistent outcomes [33,34] and an increased risk of postoperative complications compared with OA and cuff arthropathy [35]. Additionally, shoulder arthroplasty for fracture seems to lead to an even higher resource utilization [36], which is especially important as we documented a massive increase in these procedures in the upcoming decades, probably affecting future healthcare costs.…”
Section: Projections As a Function Of Age And Indicationmentioning
confidence: 99%
“…In complex proximal humerus fractures, which represent the third-most common fracture seen in patients aged > 60 years [30], rTSA was found to provide more reproducible function with better recovery, as well as lower revision rates than HA [31,32]. However, recent studies also suggest, that shoulder arthroplasty due to fracture could be associated with more inconsistent outcomes [33,34] and an increased risk of postoperative complications compared with OA and cuff arthropathy [35]. Additionally, shoulder arthroplasty for fracture seems to lead to an even higher resource utilization [36], which is especially important as we documented a massive increase in these procedures in the upcoming decades, probably affecting future healthcare costs.…”
Section: Projections As a Function Of Age And Indicationmentioning
confidence: 99%
“…The indication for surgery has also been shown to be a risk factor for periprosthetic shoulder infection. Multiple studies have shown arthroplasty for treatment of a proximal humerus fracture has a higher risk of PJI, with 3-4 times greater risk compared with other surgical indications [4,35]. Revision shoulder arthroplasty has also been shown to be a risk factor for PJI [9,19].…”
Section: Treatment Factorsmentioning
confidence: 99%
“…As shoulder arthroplasty becomes an increasingly popular option for patients with degenerative conditions of the shoulder, identifying risk factors for adverse perioperative outcomes remains a priority in this setting. While a wide variety of research studies have examined postoperative outcomes both in terms of functionality and complications, 2 , 6 , 23 , 24 , 25 , 32 few groups have examined the incidence and risk factors for intraoperative fractures. Despite their relative infrequency, patients and providers alike may benefit from this information for use during the preoperative counseling process.…”
Section: Discussionmentioning
confidence: 99%